(untitled) (Pesquisa Odontológica Brasileira, 2003)
The vascular changes in the subcutaneous connective tissue of rats induced by dentin bonding systems (one step) was studied and compared to those induced by saline solution (negative control) and Furacin (positive control), during the exudative phase of the inflammatory process. Twenty mg/kg of Evan's blue were injected intravenously in the vein of the rats' penises; 0.1 ml of each substance tested was inoculated in the subcutaneous tissue. After a 3 hour period the animals were sacrificed and their skins were excised and punched out with a standard steel 2.5 cm in diameter. The specimens were immediately immersed in 8 ml of formamide and taken to a double boiler for 72 hours at 37ºC, to remove the dye. The liquid containing the overflowed dye was filtered, analyzed in the spectrophotometer (620 nm) and classified according to the criteria established by Nagem-Filho, Pereira (1976). After statistical analysis, the irritative potential of the substances was ranked as follows: Furacin (severe) >; Single Bond and Bond 1 (moderate - no significant differences between the dentin bonding systems tested) >; saline solution (not significant as regards the irritation degree).